2008
DOI: 10.1007/s10705-008-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between legume technologies and fallow, and their effects on maize and soil traits, in two distinct environments of the West African savannah

Abstract: Legume-maize rotation and maize nitrogen (N)-response trials were carried out simultaneously from 1998 to 2004 in two distinct agro-ecological environments of West Africa: the humid derived savannah (Ibadan) and the drier northern Guinea savannah (Zaria). In the N-response trial, maize was grown annually receiving urea N at 0, 30, 60, 90 and 120 kg N ha -1. In Ibadan, maize production increased with N fertilization, but mean annual grain yield declined over the course of the trial. In Zaria, no response to N t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…2) and had stronger effects in the poor fertility fields which were often P deficient (Table 1). Millet yields increased following legumes, as is commonly found in legume cereal cropping systems (Osunde et al 2003;Ncube 2007;Franke et al 2008). The yield responses were larger when larger amounts of legume biomass were incorporated.…”
Section: Discussionmentioning
confidence: 91%
“…2) and had stronger effects in the poor fertility fields which were often P deficient (Table 1). Millet yields increased following legumes, as is commonly found in legume cereal cropping systems (Osunde et al 2003;Ncube 2007;Franke et al 2008). The yield responses were larger when larger amounts of legume biomass were incorporated.…”
Section: Discussionmentioning
confidence: 91%
“…At both locations, aboveground soybean residues were fed to steers over the dry season and the manure was collected and applied in the field at subsequent planting. Plant residue and manure analyses suggested that the carry-over rate of N from residues at harvest to manure at planting was 0.50 (Franke et al 2008), and this rate was used in N budget (3).…”
Section: Calculation Of N Budgetsmentioning
confidence: 99%
“…The crop accumulated 55 kg aboveground N ha -1 . Soybean was heavily infested with diseases in Ibadan (Franke et al 2008) and as a result, biomass production was reduced and leaves prematurely shattered.…”
Section: Biomass Yield N Yield and Symbiotic N Fixationmentioning
confidence: 99%
See 2 more Smart Citations